2019
DOI: 10.1136/bmjebm-2019-111208
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic peptide-guided treatment for heart failure: a systematic review and meta-analysis

Abstract: BackgroundGUIDE-IT, the largest trial to date, published in August 2017, evaluating the effectiveness of natriuretic peptide (NP)-guided treatment of heart failure (HF), was stopped early for futility on a composite outcome. However, the reported effect sizes on individual outcomes of all-cause mortality and HF admissions are potentially clinically relevant.ObjectiveThis systematic review and meta-analysis aims to combine all available trial level evidence to determine if NP-guided treatment of HF reduces all-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 23 publications
0
15
0
2
Order By: Relevance
“…The evidence endorsing the utility of NPs for guiding therapy is mixed. The largest trial and the more recent meta‐analysis showed no prognostic benefit compared to usual care 42,43 . The GUIDE‐IT included 894 patients with stable LV ejection fraction ≤40% and elevated NT‐proBNP in the previous month 43 .…”
Section: Role Of Circulating Biomarkers For Assessing the Severity An...mentioning
confidence: 99%
“…The evidence endorsing the utility of NPs for guiding therapy is mixed. The largest trial and the more recent meta‐analysis showed no prognostic benefit compared to usual care 42,43 . The GUIDE‐IT included 894 patients with stable LV ejection fraction ≤40% and elevated NT‐proBNP in the previous month 43 .…”
Section: Role Of Circulating Biomarkers For Assessing the Severity An...mentioning
confidence: 99%
“…Acute decreases in renal function after ADHF undergoing aggressive decongestion with high-dose loop diuretics does not necessarily reflect structural injury to the kidneys [22]. Third, this "lack of effectiveness" to renal recovery was accompanied by a reduction in BNP (− 1365 ± 1574), and even during treatment it was possible to decrease BNP > 30% in 36% of cases, an event that can be interpreted as effective decongestion, that is significantly associated with greater survival in the median long term [23], and guiding the treatment of these patients with natriuretic peptides has been proven to decrease their probability of hospitalizations by 20% and their probability of dying by 13% [24].…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, uma metanálise recente, feita com 4.554 pacientes e incorporando os pacientes do estudo GUIDE-IT, mostrou redução de hospitalizações e mortalidade por todas as causas com o tratamento guiado pelos peptídeos natriuréticos. 111 IC: insuficiência cardíaca; NT: proBNP-fração N-terminal do peptídeo natriurético atrial do tipo B. A incorporação do sequenciamento de última geração têm aumentado a sensibilidade dos testes genéticos, possibilitando o diagnóstico precoce com perspectiva de intervenção.…”
Section: No Estudo Prove-hf (Association Of Change In N-terminal Pro-b-type Natriuretic Peptide Following Initiation Of Sacubitril-valsarunclassified